Control of Herpes Simplex Virus Replication Is Mediated through an Interferon Regulatory Factor 3-Dependent Pathway - Menachery, Vineet D. (American Society for Microbiology (ASM), 2009)
The type I interferon (IFN) cascade is critical in controlling viral replication and pathogenesis. Recognition pathways triggered by viral infection rapidly induce the type I IFN cascade, often in an IFN regulatory factor 3 (IRF-3)-dependent fashion. This dependence predicts that loss of IRF-3 would render early recognition pathways inoperative and thereby impact virus replication, but this has not been observed previously with herpes simplex virus type 1 (HSV-1) in vitro. In this study, HSV-1-infected IRF-3(−/−) bone marrow-derived dendritic cells (BMDCs) and macrophages supported increased HSV replication compared to control cells. In addition, IRF-3-deficient BMDCs exhibited delayed type I IFN synthesis compared to control cells. However, while IFN pretreatment of IRF-3(−/−) BMDCs resulted in reduced virus titers, a far greater reduction was seen after IFN treatment of wild-type cells. This suggests that even in the presence of exogenously supplied IFN, IRF-3(−/−) BMDCs are inherently defective in the control of HSV-1 replication. Together, these results demonstrate a critical role for IRF-3-mediated pathways in controlling HSV-1 replication in cells of the murine immune system.